2018
DOI: 10.1007/s12029-018-0126-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Left Colonic Artery Preservation on Anastomotic Leakage in Laparoscopic Sigmoid Resection and Anterior Resection for Sigmoid and Rectosigmoid Colon Cancer

Abstract: Based on the results obtained by performing laparoscopic operation for sigmoid colon cancer and rectosigmoid cancer, the LCA preservative procedure is warranted for prevention of AL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…A multicenter study also suggested that preservation of the LCA during laparoscopic AR for middle and low rectal cancers is associated with lower AL rates (7.4% vs 13.2%, P = 0.005)[ 34 ]. Several others studies have reported the same conclusion[ 35 - 37 ]. Our study also suggested a statistically higher rate of AL and diverting stoma in the HL group (10.2% vs 2.6%, P = 0.001; 16.5% vs 7.5%, P = 0.003, respectively).…”
Section: Discussionsupporting
confidence: 73%
“…A multicenter study also suggested that preservation of the LCA during laparoscopic AR for middle and low rectal cancers is associated with lower AL rates (7.4% vs 13.2%, P = 0.005)[ 34 ]. Several others studies have reported the same conclusion[ 35 - 37 ]. Our study also suggested a statistically higher rate of AL and diverting stoma in the HL group (10.2% vs 2.6%, P = 0.001; 16.5% vs 7.5%, P = 0.003, respectively).…”
Section: Discussionsupporting
confidence: 73%
“…[6] It has been suggested that the incidence of anastomotic leakage after rectal cancer surgery is related to the level of ligation of the IMA [7]. Several studies [8][9][10][11] have conflicting reports on the impact of LCA preservation on anastomotic leakage in anterior resection for rectal cancer. The use of the high ligation may provide a greater number of lymph nodes(LNs) available for histopathological examination.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, preservation of the LCA during radical resection of rectal cancer has attracted increasing attention [11,16]. Low ligation with apical LNs dissection in rectal cancer treatment provides better anastomotic blood supply but is not associated with differences in LNs retrieval rate and operation time [17].…”
Section: Introductionmentioning
confidence: 99%
“…Anastomotic leakage (AL) is a severe complication of anterior resection for rectal cancer, with an incidence varying from 3.5% to 17.4% [1–3]. Some studies [4,5] consider high ligation (HL) of the inferior mesenteric artery (IMA) as a risk factor for AL.…”
mentioning
confidence: 99%